Sistem Pemantauan Getaran Pada Jalur Soft Track Secara Online - Erna Kusuma Wati; Hari Hadi S; Ayu Maharani; Fraska Anagga (Universitas Indraprasta PGRI Jakarta, 2020)
Along with the development of toll road infrastructure, we need to anticipate and monitor the effects it causes, especially for residents living around toll roads. The impact of vibrations caused by passing vehicles can disturb the health of the population if it crosses the Maximum Threshold. Based on this, during this research, we will design a vibration measuring device that can be monitored online by the vibration (acceleration). The vibration meter has been designed using the MMA7361 accelerometer sensor. Data transmission is carried out online using the ESP8266 WiFi module and using a portable WiFi hotspot source from a cellular phone. The measurement was carried out for about 30 minutes at the edge of the Jakarta-Serpong toll road, precisely at Km-11. By using four vibration measurement sensors, the sensor distance variations are carried out on toll roads, the distance between each sensor is as far as 3 meters. The results of measurement and testing of vehicle vibrations passing on the Sepong-Jakarta toll road on the four sensors show an acceleration value of <0.45m / s². The measurement results of the vibration of vehicles passing on the Jakarta-Serpong Km 11 toll roadshow that the resulting acceleration value is <0.45m / s². Based on the level of risk of exposure to vibration for health, the acceleration value is in a low category so that the toll lane distance is in a safe zone for the health of the surrounding population.